11 Predicting the outcome of reperfusion acutely in patients with STEMI – derivation and validation of the ATI score. (24th April 2016) - Maria, Giovanni Luigi De; Fahrni, Gregor; Alkhalil, Mohammad; Cuculi, Florim; Dawkins, Sam; Wolfrum, Mathias; Choudhury, Robin P; Forfar, John C; Prendergast, Bernard D; Yetgin, Tuncay; Geuns, Robert Jan van; Tebaldi, Matteo; et al.
Abstract : Aim: Restoration of effective myocardial reperfusion by primary percutaneous coronary intervention (PPCI) in patients with STEMI is not predictable. A method to assess the likelihood of a suboptimal response to conventional pharmaco-mechanical therapies could be beneficial. We aimed to derive and validate a scoring system that can be used acutely at the time of coronary reopening to predict the likelihood of downstream microvascular impairment in patients with STEMI. Methods and Results: A score estimating the risk of post-procedural microvascular injury defined by an index of microcirculatory resistance (IMR) > 40, was initially derived in a cohort of 85 STEMI patients (Derivation cohort). This score was then tested and validated in three further cohorts of patients (Retrospective (30 patients), Prospective (42 patients) and External (29 patients). The ATI score [Age ( > 50 = 1); pre-stenting IMR (> 40 and < 100 = 1; ≥ 100 = 2); Thrombus score (4=1; 5=3)] was highly predictive of a post-stenting IMR > 40 in all the four cohorts (AUC:0.87; p < 0.001-Derivation cohort, 0.84; p: 0.002-Retrospective cohort, 0.92; p < 0.001-Prospective cohort and 0.81; p: 0.006-External cohort). In the whole population an ATI score ≥ 4 presented a 95.1% risk of final IMR >40, while no cases of final IMR >40 occurred in the presence of an ATI score < 2. Conclusions: The ATI score appears to be a promising tool capable of identifying patients during PPCI that are at the highest risk of an adverse outcome following revascularisation.